2021
DOI: 10.1186/s12302-021-00515-w
|View full text |Cite
|
Sign up to set email alerts
|

Toxic effects of UV filters from sunscreens on coral reefs revisited: regulatory aspects for “reef safe” products

Abstract: Background Tropical coral reefs have been recognized for their significant ecological and economical value. However, increasing anthropogenic disturbances have led to progressively declining coral reef ecosystems on a global scale. More recently, several studies implicated UV filters used in sunscreen products to negatively affect corals and possibly contribute to regional trends in coral decline. Following a public debate, bans were implemented on several organic UV filters and sunscreen produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 54 publications
1
48
0
Order By: Relevance
“…These data have raised alarms regarding toxicity towards humans and the environment [15], which have led some tropical places to ban four organic filters, thus, generating an alarm towards this type of substance [16]. An approach pursued in recent times is the search for new, natural, environmentally friendly molecules of an organic nature that can perform as sunscreen (UV) filters.…”
Section: Introductionmentioning
confidence: 99%
“…These data have raised alarms regarding toxicity towards humans and the environment [15], which have led some tropical places to ban four organic filters, thus, generating an alarm towards this type of substance [16]. An approach pursued in recent times is the search for new, natural, environmentally friendly molecules of an organic nature that can perform as sunscreen (UV) filters.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative comparisons with previous studies are difficult due to methodological and analytical inconsistencies, and due to the lack of analytical verification of exposure concentration in various previous studies as discussed in recent literature [ 49 , 50 , 51 , 52 ]. Up to this date, only two other studies performed toxicity assays with UV filters on coral larvae.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Downs et al [ 36 ] reported mortality in coral larvae of Stylophora pistillata a LC 50 (i.e., concentration that kills 50% of the population) at nominal 139 µg L −1 after exposure to the organic UV filter benzophenone-3 (BP3 or oxybenzone). Based on these studies, policymakers in various locations (i.e., Hawaii, US Virgin Islands, Palau, Aruba and Bonaire) have already taken regulatory actions and banned the use of some organic UV filters including BP3, ethylhexyl methoxycinnamate (EHMC or octinoxate), octocrylene (OCR) and 4-methylbenzylidene camphor (4MBC) in sunscreens [ 49 , 50 , 51 ]. Those bans, however, are controversial as the underlying studies revealed several shortcomings (e.g., lack of analytical verification of exposure concentrations, inadequate controls, lack of environmental relevance) that question the reliability of some of the test results and the conclusions drawn within these studies [ 49 , 50 , 51 , 52 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations